2019
DOI: 10.4236/as.2019.108084
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Residual Effects of Different Levels of Chicken Manure Fertilization on the Growth and Biomass Production of <i>Brachiaria ruziziensis</i> (Poaceae) at the Bolting in West Cameroon

Abstract: The direct and residual effects of different levels of chicken manure fertilization on the growth and biomass production of B. ruziziensis at the bolting were studied in West Cameroon. The objective of this study was to evaluate the effects of different levels of chicken manure fertilization on the growth and biomass production of Brachiaria ruziziensis at the bolting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…It improves the holding capacity of soil and increases the availability of elements for grasses (Hamaiel et al, 2015;Shokri, 2020). These findings are in close conformity with those of (Azangue et al, 2019) in west Cameroon, who reported the height of Brachiaria ruziziensis supplemented with chicken manure produced a tiller height of 157.47 cm which was significantly higher compared with the control which produced tiller with height of 153. Hybrid brachiaria with manure plants that received bovine manure achieved the highest height (average value of 96.06 cm) compared to those that had mycorrhizae (average value of 84 cm).…”
Section: Effect Of Organic Manure On the Number Of Tiller Of Brachiar...supporting
confidence: 91%
“…It improves the holding capacity of soil and increases the availability of elements for grasses (Hamaiel et al, 2015;Shokri, 2020). These findings are in close conformity with those of (Azangue et al, 2019) in west Cameroon, who reported the height of Brachiaria ruziziensis supplemented with chicken manure produced a tiller height of 157.47 cm which was significantly higher compared with the control which produced tiller with height of 153. Hybrid brachiaria with manure plants that received bovine manure achieved the highest height (average value of 96.06 cm) compared to those that had mycorrhizae (average value of 84 cm).…”
Section: Effect Of Organic Manure On the Number Of Tiller Of Brachiar...supporting
confidence: 91%
“…Effects of the different levels of fertilization to the hen droppings on the average contents of ash and crude protein (% DM) of P. clandestinum cut every thirty days 13…”
mentioning
confidence: 99%